Study of organic residues in vessels of archaeological origin with physicochemical analytical techniques - Koupadi Kyriaki (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This poster presents the physicochemical analysis results of the organic residues from copper alloy artifacts dated between 5th and 7th cent. A.D. FT-IR and GC–MS were used to identify the composition of the residues. Biomarkers of pine resins were identified in one sample, while a broad range of oils and fats, along with their degradation products, were identified in all samples and associated with the presence of vegetable oil extracted from plants of the Brassicaceae family.